2021
DOI: 10.1177/0363546520987819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medialization of the Trochlear Groove and Lateralization of the Tibial Tubercle on TT-TG Distance: A Cross-sectional Study of Dysplastic and Nondysplastic Knees

Abstract: Background: Tibial tubercle–trochlear groove (TT-TG) distance is often used as a measure of lateralization of the TT and is important for surgical planning. Purpose: To investigate if increased TT-TG distance measured on axial magnetic resonance images is due to lateralization of the TT or medialization of the TG. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 84 knees (28 normal [NK], 28 with trochlear dysplasia [TD], and 28 with patellar dislocation without TD [PD]) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
0
27
2
Order By: Relevance
“…13,14,29,38 Liu et al 27 reported successful outcomes with an isolated MPFL reconstruction in the presence of trochlear dysplasia; however, Hopper et al 19 and Wagner et al 44 demonstrated worse outcomes after an isolated MPFL reconstruction in patients with trochlear dysplasia, particularly that classified as Dejour C and D. Some advocate for tibial tubercle anteromedialization in the setting of trochlear dysplasia, but recent literature suggests that patients with trochlear dysplasia in fact have a more medialized trochlear groove as opposed to a lateralized tibial tubercle. 31 This suggests that there is still much to learn about this disorder and how to adequately treat symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,29,38 Liu et al 27 reported successful outcomes with an isolated MPFL reconstruction in the presence of trochlear dysplasia; however, Hopper et al 19 and Wagner et al 44 demonstrated worse outcomes after an isolated MPFL reconstruction in patients with trochlear dysplasia, particularly that classified as Dejour C and D. Some advocate for tibial tubercle anteromedialization in the setting of trochlear dysplasia, but recent literature suggests that patients with trochlear dysplasia in fact have a more medialized trochlear groove as opposed to a lateralized tibial tubercle. 31 This suggests that there is still much to learn about this disorder and how to adequately treat symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the TT-TG distance in predicting recurrent LPD is controversial. 20 Paiva et al 31 showed that the TT-TG distance was increased in patients with trochlear dysplasia due to medialization of the trochlear groove. In contrast, the TT-PCL distance is independent of any femoral reference point to detect lateralization of the tibial tubercle, which did not differ between patients groups with and without recurrent LPD in our study.…”
Section: Discussionmentioning
confidence: 99%
“…TT-TG distance was first introduced by Dejour et al 2 to assess the quadriceps vector as a risk factor for patellar instability. An increased value was originally assumed to be caused by lateralization of the tibial tubercle 21,45 . However, TT-TG distance in the present study was more strongly and positively affected by trochlear groove medialization than by tibial tubercle lateralization.…”
Section: Discussionmentioning
confidence: 99%